Large Language Models as a New Tool in Modern Media Communications - Vasilev Andrei Mikhailovich; Trofimova Galina Nikolayevna (مجلة النور للدراسات الانسانية)
The widespread application of digital technology has triggered profound changes in the field of education, promoting the innovation and transformation of the education model, and international organizations have deeply discussed and given creative suggestions on sensitive topics such as when and how artificial intelligence can be used in education. This paper focuses on the latest norms proposed by UNESCO, the OECD and the EU on the application of AI in education,